INFLUENCE OF COLLABORATION ON THE IMPACT OF PUBLICATION AT DIFFERENT LEVELS OF AGGREGATION: analysis of Spanish research on Marine Science - Costas, Rodrigo (PontodeAcesso, 2012)
This paper presents a bibliometric analysis of the scientific activity of Spain in Marine Science through the analysis of its publications in the Science Citation Index during the period 1994-2004. The evolution of collaboration over the period and the influence of different types of collaboration on the impact of research are studied. Spanish production accounts for 6,898 publications. An increment in the number of publications and in the impact of the publication journals over time is observed. Internationally-coauthored publications increase faster than those with national or with no collaboration at all and tend to be published in more prestigious journals and to receive a higher number of citations. The indicators “gain in impact factor” and “gain in citations” are used to measure the effects of different types of collaboration over the impact of the research for the main institutional sectors in the country, main research centres and most productive scientists. A positive effect of collaboration over the impact of research is observed, but as the aggregation level of analysis decreases this positive effect is less clear. In the case of individual scientists this good relationship between international collaboration and impact of publications is not always observed.